Lipoprotein lipase in hemodialysis patients: indications that low molecular weight heparin depletes functional stores, despite low plasma levels of the enzyme - Näsström, Birgit (BioMed Central, 2004)
BACKGROUND: Lipoprotein lipase (LPL) has a central role in the catabolism of triglyceride-rich lipoproteins. The enzyme is anchored to the vascular endothelium through interaction with heparan sulphate proteoglycans and is displaced from this interaction by heparin. When heparin is infused, there is a peak of LPL activity accompanied by a reduction in triglycerides (TG) during the first hour, followed by a decrease in LPL activity to a stable plateau during the remaining session while TG increase towards and beyond baseline. This suggests that tissue stores of LPL become depleted. It has been argued that low molecular weight (LMW) heparins cause less disturbance of the LPL system than conventional heparin does. METHODS: We have followed LPL activity and TG during a dialysis-session with a LMW heparin (dalteparin) using the same patients and regime as in a previous study with conventional heparin, i.e. a primed infusion. RESULTS: The shape of the curve for LPL activity resembled that during the earlier dialyses with conventional heparin, but the values were lower during dialysis with dalteparin. The area under the curve for LPL activity during the peak period (0–180 minutes) was only 27% and for the plateau period (180–240 minutes) it was only 36% of that observed with conventional heparin (p < 0.01). These remarkably low plasma LPL activities prompted us to re-analyze LPL activity and to measure LPL mass in frozen samples from our earlier studies. There was excellent correlation between the new and old values which rules out the possibility of assay variations as a confounding factor. TG increased from 2.14 mmol/L before, to 2.59 mmol/L after the dialysis (p < 0.01). From 30 minutes on, the TG values were significantly higher after dalteparin compared to conventional heparin (p < 0.05). CONCLUSION: These results indicate that LMW heparins disturb the LPL system as much or more than conventional heparin does.